Anthropological research in Central Asia: the experience of Uzbekistan - Sulaymanov, Amaliddin Nurboyevich (The Lingua Spectrum, 2026)
This article scientifically analyzes the stages of formation and development of the science of anthropology in Uzbekistan. The study covers the formation of anthropological research in the region since the beginning of the 20th century, the emergence of scientific schools, and the scientific activities of scientists who contributed to the development of the field. In particular, special attention is paid to the anthropological research, expeditions, and work on the study of the anthropological and ethnic history of the peoples of the region conducted by L.V. Oshanin and his students. The stages of development of the science of anthropology in Uzbekistan, areas of scientific research, and their results are also analyzed. The article reveals the scientific significance of the science of anthropology in studying the ethnogenesis, anthropological composition, and historical development of the peoples of the region.